Роздiлення iзотопiв у системi iз зустрiчними магнiтними полями у вiдбитому потоцi - Belikov, A. G.; Papkovich, V. G. (Publishing house "Academperiodika", 2019)
The isotope separation in a reflected ion beam injected into a cusp magnetic field has been considered. The magnetic field configuration was formed by two rings with oppositely directed currents. The motion of the particles entering the system and reflected by the increasing magnetic field of the second ring is numerically calculated. A possibility for reflected particles to be separated in the radial direction is shown. This effect allows an annular ion source to be used, which leads to an increase in the total current and the performance of the system.